Toward the reliable diagnosis of DSM-5 premenstrual dysphoric disorder: the Carolina Premenstrual Assessment Scoring System (C-PASS) - Eisenlohr-Moul, Tory A.; Schmalenberger, Katja (The American journal of psychiatry, 2017)
Objective: Despite evidence for the validity of premenstrual dysphoric disorder (PMDD) and the inclusion of the disorder in DSM-5, variable diagnostic practices compromise the construct validity of the diagnosis and threaten the clarity of efforts to understand and treat its underlying pathophysiology. In an effort to hasten and streamline the translation of the DSM-5 criteria for PMDD into terms compatible with existing research practices, the authors present the development and initial validation of the Carolina Premenstrual Assessment Scoring System (C-PASS). The C-PASS (available as a worksheet, Excel macro, and SAS macro) is a standardized scoring system for making DSM-5 PMDD diagnoses using two or more months of daily symptom ratings with the Daily Record of Severity of Problems (DRSP). Method: Two hundred women recruited for retrospectively reported premenstrual emotional symptoms provided two to four months of daily symptom ratings on the DRSP. Diagnoses made by expert clinician and by the C-PASS were compared. Results: Agreement of C-PASS diagnosis with expert clinical diagnosis was excellent; overall correct classification by the C-PASS was estimated at 98%. Consistent with previous evidence, retrospective reports of premenstrual symptom increases were a poor predictor of prospective C-PASS diagnosis. Conclusions: The C-PASS is a reliable and valid companion protocol to the DRSP that standardizes and streamlines the complex, multilevel diagnosis of DSM-5 PMDD. Consistent use of this robust diagnostic method would result in more clearly defined, homogeneous samples of women with PMDD, thereby improving the clarity of studies seeking to characterize and treat the underlying pathophysiology of the disorder.